Valoriser le patrimoine culturel pyrénéen à l’aide d’une plateforme et d’une application mobile - Landy Rajaonarivo; Marie-Noëlle Bessagnet; Christian Sallaberry; Annig Le Parc Lacayrelle; Philippe Roose (Humanités Numériques)
TCVPYR is a European FEDER project which aims to promote tourism in the French Pyrenees region by leveraging its cultural heritage. It involves scientists from various domains: geographers, historians, anthropologists, and computer scientists. This paper presents two approaches to exploit cultural heritage points of interest (POI), both using Web of data concepts. One consists in publishing these data into the database of well-known open data platforms such as Wikipedia. The other one consists in an open source mobile application dedicated to touristic itineraries. The first approach involves a fully automated process to publish any dataset on Wikipedia. Thanks to a proof of concept (POC), we validate this process on a sample of geo-referenced cultural heritage data collected by TCVPYR researchers in different regions of the Pyrenees. These same data are also highlighted in the second approach via a mobile application recommending personalised touristic itineraries.